Individual and Cultural Differences in Attentional Learning - Mah, Sue Lynn (2022)
Associative learning phenomena have been widely used to understand the deficits in selective attention in schizophrenia by using the personality trait, schizotypy, as a proxy. However, other personality traits such as anxiety and the Big 5 personality traits have been under-looked despite a comorbidity between schizophrenia/schizotypy and anxiety as well as the psychopathology links of the Big 5 traits. Moreover, there is evidence of different thinking styles exhibited by different cultures (e.g., individualistic and collectivistic cultures), where the majority of members in an individualistic culture learn and think in an analytical/elemental manner while the majority of members in a collectivistic culture have a predisposition to think and learn holistically/configurally. It is therefore proposed that other personality traits and cultural differences in thinking/learning can explain conflicting evidence found in the schizotypy and associative learning literature. Previous studies of variations in attention-driven associative learning have demonstrated an emphasis on latent inhibition and less so on blocking and learned predictiveness. Furthermore, there are very few studies that have attempted to reproduce two learning effects within the same individual. Therefore, Study 1 aimed to create a paradigm which can generate the effects of blocking and learned predictiveness within the same participant to first, fill the gap in the literature, and second, to develop a better, converging, understanding of the role of attention in learning. The results of this study found an effect of learned predictiveness but no effect of blocking. It was proposed that the effect of learned predictiveness somehow masked the effect of blocking, so Study 2 aimed to replicate the previous study but with only the blocking trials. The results still showed no blocking effect despite the removal of the learned predictiveness trials. There was a possibility that a within-compound association effect was the reason why blocking was not found. Therefore, in Study 3, the design of Study 2 was replicated but now with an addition of a Stage 3 where the blocked stimuli’s contingencies were switched, and if there really was a within-compound association, the ratings for these blocked stimuli would be reduced compared to the first test stage. The results showed at test stage 1, the ratings for the control stimuli were lower than the blocked stimuli, replicating results of Study 2. At test stage 2, with a change in contingency from Stage 3, the ratings for the blocked stimuli were reduced but it was still higher than the control stimuli, suggesting a within-compound association. Study 4 aimed to use a simpler blocking design (Kamin, 1969) to determine if the previous design used was too complicated. While there the ratings for the control stimuli were higher than the blocked stimuli, a paired samples t-test revealed no significance. The results from Studies 1-4 can be explained using acquired distinctiveness/acquired equivalence theories and the redundancy effect. Since attempts to demonstrate a blocking effect throughout Study 1 to 4 failed, Study 5 aimed to generate the effects of latent inhibition and learned predictiveness using a letter prediction task (Granger et al., 2016) and a food allergist task (Le Pelley and McLaren, 2003). Personality traits including the Big 5, schizotypy and anxiety were also measured. The participants were divided into individualistic and collectivistic groups using Hofstede’s database which sorts individuals via their nationalities. The results initially showed that participants, overall, exhibited both latent inhibition and learned predictiveness. When split by culture, only participants from the individualistic group showed both effects while participants from the collectivistic group showed only latent inhibition. There was also no correlation between latent inhibition and learned predictiveness overall and within groups. Moreover, there was an effect of impulsive nonconformity that was related to a greater magnitude of latent inhibition in the individualistic group. It was also found that participants high in conscientiousness from the individualistic group learned more about the relevant stimuli in the learned predictiveness task but participants from the collectivistic group learned about the relevant stimuli less. There was no evidence of anxiety predicting latent inhibition or learned predictiveness. Since Study 5 was exploratory by nature, Study 6 aimed to replicate the findings but specifically focussing on the relationship between personality traits and culture in latent inhibition. It could be seen from the results of this current study that latent inhibition was observed in both the individualistic and collectivistic group, replicating Study 5. This study was also conducted online due to Covid-19 and the results demonstrated that there was no difference in response times between the lab-based task and this online version. The effect of impulsive nonconformity predicting enhanced latent inhibition in participants from the individualistic group found in Study 5 was not replicated. Instead, it was revealed that conscientiousness predicted latent inhibition in the individualistic group and openness predicted latent inhibition in the collectivistic group. There was again no evidence of anxiety being related to the magnitude of latent inhibition. Study 7 was a replication of Study 5, but specifically investigating the relationship between the Big 5, schizotypy and cultural orientation and learned predictiveness. Since there were limitations to sorting participants into individualistic and collectivistic groups with their nationalities (Cohen, 2009; Kitayama and Uskul, 2011; Maisuwong, 2012), a cultural orientation questionnaire (Sharma, 2010) was employed to provide a more accurate measure of trait individualism and collectivism to provide further validity to the results found. The results showed a learned predictiveness effect in the individualistic group but not the collectivistic group, replicating results from Study 5. The effect of conscientiousness predicting the learning of relevant stimuli was not replicated but an effect of extraversion positively predicting the learning of irrelevant stimuli was found within the collectivistic group. There was also an effect of introvertive anhedonia negatively predicting the learning of irrelevant stimuli in the collectivistic group. The final chapter of this thesis begins with a summary of results from all the studies. It then discusses how the individual and cultural differences exhibited by participants influenced the results throughout Studies 1-7 and provides suggestions as to why evidence from previous literature was not always consistent. The strengths and limitations faced in this thesis are discussed and suggestions for future research described.